Flipped classroom: experience of a pedagogical model adopted during the health crisis to support work-study teaching - Hommane Boudine; Meriem Bentaleb; Mourad Radi; Youssef El Madhi; Soufiane Er-rzine; Ilham Bentaleb; Mohamed Tayebi (Moroccan Journal of Quantitative and Qualitative Research, 2022)
In early 2020 new pedagogical practices and approaches were adopted to ensure the continuity of the education system during the health crisis caused by the coronavirus pandemic (covid19) to make the student more active in the new learning process. This study focuses on manipulating information and communication technologies in education (ICT) to support the pedagogical alternation between distance and face-to-face education to ensure equity and equal opportunities. The objective of this study is to assess the implementation of reverse pedagogy and the obstacles that hinder it by focusing on this new process that offers the learner the opportunity to see the course support through the digital tool, using an educational platform (Moodle), which gives each student the opportunity to learn and evolve at their own pace, without losing the motivation to learn. This research is addressed to students of the last year of the college cycle at the ALYASSAMIN school in Sidi Slimane. The results obtained confirm that the pedagogical model of the flipped classroom ensured a stable progression of the education system during the period of the health crisis. This study is based on assessing the state of play and suggests the generalization of inverted classes and integrating them into teaching practices. In conclusion, the results presented must be considered for adapted teaching to support alternative education and to follow the current digital evolution.